Variabel Determinan Terhadap Use Behaviour Shopee Paylater Pada Kalangan Gen Z Dimoderasi Dengan Jenis Kelamin - Christian, Ryan; Nurjanah, Siti (Research and Community Service UNIVERSITAS KALBIS, 2025)
The era of digitalization has significantly transformed consumer shopping behavior, with digital financial technology emerging as the fastest-growing digital service sector in Indonesia. One of the most rapidly expanding services within this sector is the paylater service, which allows for deferred payment to be settled at a future date. This research investigates the factors influencing the adoption and use behavior of one of the largest paylater services in Indoneisa, Shopee Paylater among Generation Z, using the Extended Unified Theory of Acceptance and Use of Technology (UTAUT) model as the foundation of this reserach. This study identifies key factors such as hedonic motivation, facilitating conditions, behavioral intention, and use behavior, with gender as a moderating variable. The objective is to provide insights into Gen Z consumers' behavior in adopting Shopee Paylater, aiding service providers in understanding, adjusting, and optimizing their products towards this demographic.